Socio-Economic and Environmental Factors Influencing the Output of Rice Farmers in Kaduna State and Federal Capital Territory, Nigeria - Ajunwa, Chikezie Gabriel; Aluwong, Jeremiah Samuel; Haruna, Ojuh Ezekiel; Ayodele, Josephine Titilayo; Abah, Michael Oguche; Abdulsalam, Ize Zinnatu; Idisi, Park Odojoma; Alabi, Olugbenga Omotayo (Nepalese Journal of Agricultural Sciences, 2026)
This study investigated the socio-economic and environmental factors influencing the output of rice farmers in Kaduna State and Federal Capital Territory, Nigeria. A multi-stage sampling technique was employed to select 185 respondents. Primary data were used based on a well-structured questionnaire. The data was analyzed using descriptive and inferential statistics. The findings reveal that the majority of the farmers are female (76.22%) with an average age of 48 years. Most are married (88.11%) with an average household size of 9 persons and have spent an average of 6 years in school education.The farmers have significant farming experience (18 years) but limited access to credit (8.65%) and the average monthly income was N36, 189.8. The socio-economic factors such as age, household size and cooperative membership, along with environmental factors such as rainfall variation and heat waves significantly influence the output of rice farmers. Environmental changes significantly impact output of rice farmers, with change in temperature, heat waves, migration, loss of crop due to soil degradation and reduction in size of water bodies being the most reported issues. These changes could lead to reduced output, poor harvests, and increased health hazards. The study recommended adaptation strategies such as multiple crop types and  planting dates and mitigation efforts such as minimizing agro chemical use and reduce food and water wastage.